CARBON-BASED nanomaterials and SKIN: An overview. (30th August 2022) - Dalla Colletta, Arianna; Pelin, Marco; Sosa, Silvio; Fusco, Laura; Prato, Maurizio; Tubaro, Aurelia
Abstract: Due to their excellent physicochemical properties, carbon-based nanomaterials (CBNs) have attracted considerable attention for multiple applications, including electronics, optoelectronics, photonics and biomedicine. An active area of research is related to their potential exploitation at the skin level, mainly as wearable and stretchable electronic devices for health-care monitoring, cosmetics, sunscreens, but also in the field of regenerative medicine for wound healing. These applications and the potential occupational exposure to CBNs during their manufacturing can lead to a significant skin contact as one of the major but underestimated exposure routes for humans, raising concern for possible adverse effects. This issue motivated an up-to-date revision of the available toxicological data on the effects of CBNs (fullerenes, carbon-nanotubes, graphene-based materials, carbon nano-onions and carbon nano-horns) after cutaneous exposure. The review is focused on the main adverse outcomes at the skin level (irritation, corrosion, sensitization, phototoxicity and relevant mechanisms) as available evidences useful to address human health risk issues related to CBNs. Currently, toxicity data on CBNs are very scarce, representing only 3.8% of total publications on CBN-based skin applications. Among all CBNs, the main data are available for fullerenes and carbon-nanotubes, with very scanty or no information for the others. Although some of them (e.g., fullerenes or some kinds of carbon-nanotubes) appear skin biocompatible, available toxicological data are not sufficient to fully characterize the hazard posed at the cutaneous level. Therefore, toxicological studies on CBN skin applications need to be implemented, enabling their wide and safe use. Graphical abstract: Image 1